"Factors influencing the outcome of COVID-19 patients admitted in a tertiary care hospital, Madurai.- a cross-sectional study" - S. Priya; M. Selva Meena; J. Sangumani; Prabhakaran Rathinam; C. Brinda Priyadharshini; V. Vijay Anand (Elsevier, 2021)
Introduction: COVID19* is a new disease with significant mortality risk. Because of the scarcity of the study on factors associated with the mortality in Tamil Nadu present study was done to determine the factors associated with the outcome of the COVID19 patients admitted in a tertiary care hospital, Madurai. Methodology: 4530 lab confirmed COVID19 patients admitted from March to August 31st, 2020; excluding the non-responders or who gave incomplete information were included in the study. Data retrieved from Case Investigation Forms *filled through telephonic interview. Chi -square test, Univariate and multivariate logistic regression were used to find out the association between the factors and risk of death(outcome). Results: Out of 4530 COVID19 positive patients 381(8.4%) died and 4149(91.6%) were discharged. Using multivariate logistic regression* following were the factors predicted to be associated with mortality:Age group <17yrs(PR = 4.12),30-44yrs(PR = 2.28),45-59(PR = 3.12),60-69(PR = 4.26) and ≥ 70(PR = 7.05); male gender(PR = 1.26); breathlessness at the time of admission(PR = 7.05); with 1symptom (PR = 2.58), 2symptoms(PR = 3.16) and ≥ 3 symptoms(PR = 2.45); chronic kidney disease(PR = 3.07), malignancy(PR = 2.39); other chronic diseases(PR = 1.89); having only diabetes(PR = 1.58); diabetes with hypertension (PR = 1.70); diabetes with heart disease(PR = 1.94); Hypertension with heart disease(PR = 2.30); diabetes with hypertension and heart disease(PR = 1.58). Survival probability* was more than 90% when patient gets admitted within a week after symptom onset,<80% for between 7 and 10 days and declines thereafter. Conclusion: Early insights into factors associated with COVID-19 deaths have been generated in the context of a global health emergency *which may help the treating physician.